The wellbeing implications of thinking about schoolwork during leisure time: a qualitative analysis of Canadian university students' psychological detachment experiences. Issue 6 (3rd July 2021) - Luta, Denisa; Pogrebtsova, Ekaterina; Provencher, Yannick
ABSTRACT: It has been well established that psychological detachment from work (i.e., mentally separating oneself from work) during leisure time is critical in promoting employees' work performance and subjective wellbeing. This employee-focused literature presents an opportunity to extend the exploration of the salubrious experience of psychological detachment to university students. Using a qualitative design, we examined students' perceptions of their leisure time experiences. Over the course of four focus groups, we asked 25 students from a medium-sized public Canadian university to describe how they spend their leisure time, to what extent they think about or engage in schoolwork during leisure, and how their various leisure activities impact their wellbeing and academic performance. All focus groups were recorded, transcribed verbatim, and coded for patterns relating to these research questions. Our thematic analysis revealed that psychological detachment is applicable to university students; we present five themes that exemplify students' experiences with and perceived importance of psychological detachment, with implications for promoting students' wellbeing and academic performance that have been unaddressed in the psychological detachment research to date. Practically, the results provide preliminary insight into how and under what conditions psychological detachment can help students gain the most value from their leisure time.